Designing a new scalable load test system for distributed environment - Emu, Md. Azizul Haque; Mahmood, Miraj; Asif, Mohtasin Mehmod; Tanvir, Abdur Rob; Joyeeta, Raunaq Sayiara (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.